ASSOCIATION BETWEEN DIABETES AND SKIN COMPLICATIONS A STUDY ON DIABETIC DERMOPATHY IN TERTIARY CARE PATIENTS. : JPUMHS; 2024:14:03,69-76.http://doi.org/10.46536/jpumhs/2024/14.03.537 - Hira Shafquat Memon1, Quratulain Memon2, Abeer Memon3, Erum Ellahi4, Beenish Tahir5, Areej Muhammad6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
ABSTRACT BACKGROUND: Diabetic dermopathy DD is a common cutaneous manifestation of diabetes, often associated with poor glycemic control and microvascular complications. This study aimed to assess the prevalence, characteristics, and related biochemical parameters of DD in diabetic patients. METHODS: A cross-sectional study was conducted at LUMHS, Jamshoro, and LUH, Hyderabad, from January 2024 to September 2024, involving 338 diabetic patients. Clinical examinations were performed to document skin lesions’ characteristics, including size, distribution, and severity. Biochemical analysis included fasting blood glucose, HbA1c, lipid profile, microalbumin, and serum insulin levels. Histopathological examination was performed on biopsies from severe cases to confirm diagnosis. Statistical analysis involved descriptive statistics, t-tests for group comparisons, and Fisher’s exact test for small sample sizes to explore the association between DD severity and biochemical parameters. RESULTS: The prevalence of DD was 33%, with lesions primarily characterized as round, atrophic, brownish-red patches on the shins. Patients with DD had significantly higher HbA1c levels mean ± SD: 9.0 ± 1.0% compared to those without 7.5 ± 1.0%, p < 0.001. Biopsy findings in severe cases showed epidermal thinning and microangiopathy. A significant association was noted between poor glycemic control HbA1c > 8.5% and the presence of DD. CONCLUSION: This study reinforces the association between diabetic dermopathy and poor glycemic control, highlighting the need for regular monitoring and optimal diabetes management. The findings emphasize the importance of recognizing DD as a marker for underlying microvascular complications. Future research should investigate the role of ethnic and genetic factors in the variability of DD presentations.